(untitled) (ILMIY TADQIQOTLAR VA YANGI OLAM, 2025)
This article studies the functional and conceptual role of simile in shaping the notion of narcissism in Ramani Durvasula’s book It’s Not You. As a clinical psychologist and popular science communicator, Durvasula employs simile not just as a stylistic device but as a cognitive tool that structures readers’ understanding of narcissistic behavior, trauma responses, and relational dynamics. Through a qualitative philological analysis, the study identifies key simile patterns that interpret complex psychological phenomena into accessible images, this way reinforcing the conceptual frame of narcissism as manipulative, destructional, cyclical, and emotionally erosive. The findings highlight how simile operates as a conceptual bridge between psychological terminology and the reader’s experiential knowledge, making the book both rhetorically persuasive and pedagogically effective.